Ticket to Ride: A Journey Through the Most In-Demand Soft Skills for QA Professionals in Brazil - Lancetti, Wagner; Endo, Andre Takeshi; Ferrari, Fabiano Cutigi; Durelli, Vinicius (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
Background: Software quality assurance (QA) is carried out in tandem with software development. Essentially, QA activities are conducted in hopes of assessing the extent to which a software product aligns with predefined requirements. Although QA includes highly technical tasks, much like software development, it remains largely a human-centered endeavor. Consequently, soft skills can play a significant role in contributing to the success of a project and product quality, as well as boosting the productivity of QA professionals. Aim: Our objective is to investigate: (i) the most sought-after soft skills for QA professionals, (ii) potential correlations among these in-demand soft skills, (iii) variations in soft skill requirements based on the seniority level of positions, and (iv) potential differences in soft skills expectations according to the size of the hiring companies. Our analysis is centered around organizations in Brazil. Method: We looked for soft skills in 253 job advertisements from Brazilian companies. Our data extraction process followed an inductive, data-driven approach that included both manual and automated steps. Results: approximately 72% of the job advertisements list at least one soft skill. We identified 35 soft skills, among which communication-related soft skills appear to be the most sought-after. We found that companies of all sizes highly value communication skills for QA professionals at every career stage. Conclusions: Our findings underscore the critical role of communication skills. The results of our study hold potential value for QA professionals in Brazil seeking to enhance their employability and provide insights to those tasked with staffing, curriculum design, and professional development.